Acetylcholine and bradykinin induce paradoxically amplified hypotensive response in hypertensive NO-deficient rats - Gerová, M (Physiological research, 1999)
The hypotensive response to acetylcholine and bradykinin was studied in rats with NO synthase activity inhibited for a short period of 2 h or a long period of 6 weeks. N(G)-nitro-L-arginine-methyl ester (L-NAME) was used as NO synthase inhibitor (given in a dose of 50 mg/kg either into the jugular vein, or daily in drinking water). Blood pressure was measured in the right carotid artery by a Statham pressure transducer in acute experiments, and on the tail artery by the plethysmographic method weekly in chronic experiments. During both the short- and long-lasting NO synthase inhibition blood pressure rose significantly. The heart rate decreased significantly in rats treated with L-NAME for 6 weeks. Surprisingly, the hypotensive responses to acetylcholine and bradykinin were present in both experimental groups. Paradoxically, the hypotensive responses to all three doses of acetylcholine were remarkably enhanced in rats with NO synthase inhibition lasting 6 weeks, in comparison to both age-matched controls and to rats subjected to short-lasting NO synthase inhibition. The blockade of muscarinic receptors by atropine abolished the hypotensive response to acetylcholine but not to bradykinin. The hypothetical mechanisms underlying this unexpected paradoxical phenomenon of cardiovascular control are discussed.
Keywords: bradykinin; Nitric Oxide Synthase; Rats; Acetylcholine; krevní tlak; Bradykinin; NG-nitroargininmethylester; Hypertension; Atropine; Muscarinic Antagonists; acetylcholin; Rats, Wistar; mužské pohlaví; Heart Rate; krysa rodu Rattus; srdeční frekvence; synthasa oxidu dusnatého; zvířata; Blood Pressure; oxid dusnatý; Nitric Oxide; hypertenze; atropin; antagonisté muskarinových receptorů; potkani Wistar; Enzyme Inhibitors; NG-Nitroarginine Methyl Ester; Male; inhibitory enzymů; Animals